Regional Management Institute : an informal round table - Dixit, Mukund, (SAGE Knowledge. Cases., 2017)
On May 22, 2012, Prof. Chachadi, Dean, Kousali Institute of Management Studies (KIMS), Karnatak University, Dharwad, reflected on the deliberations in the previous days informal roundtable organised by him. The round table had identified several issues in sustaining management education in the regional setting. He wondered whether the issues could be resolved satisfactorily. The invitees to the round table included the heads and senior faculty members of Management Institutes located in HubliDharwad region, Karnataka State (see exhibit 1 for details), Prof. C. B. Tigadi, founding Director of KIMS, and the case writer.